The Impact of technology integration on student engagement and achievement in mathematics education: A systematic review - Muhammad Sher Baz Ali; Razia Yasmeen; Zeeshan Munawar (Researchparks Publishing, 2023)
The current research carried out a comprehensive analysis of academic research that explored the effects of technology incorporation on mathematics students' engagement and academic performance. As technology usage in education has grown more prevalent, understanding its impact on student outcomes has become increasingly significant. The primary goal of this systematic review was to examine existing research and generate a comprehensive synthesis of the outcomes. A rigorous methodology was utilized, involving a thorough examination of pertinent databases, and adhering to stringent inclusion and exclusion criteria. A quantitative approach was taken, and data were extracted utilizing a tailored data extraction form. The target population included students of all age groups enrolled in mathematics courses that integrated technology, and purposive sampling was employed as the sampling strategy. Fifteen research studies satisfied the inclusion criteria and were integrated into the final analysis. The results suggest that the integration of technology has a favorable influence on mathematics students' engagement and academic achievement. Specifically, technology integration has a noteworthy impact on student motivation, attitudes, and academic performance. The usage of technology also supports the growth of critical thinking skills and problem-solving abilities. Technology-based interventions are effective for learners of various ages and skill levels. These research findings have implications for policymakers and educators, emphasizing the prospective benefits of technology integration in enhancing student outcomes in mathematics education. Additionally, the results signal the necessity for further studies to investigate the specific means by which technology can enhance mathematics education. This systematic review presents informative insights into technology's impact on mathematics education and highlights the potential advantages of technology integration in advancing student outcomes.